Impact of Human Development and Information and Communication Technology Development Indexes on Digital Zakat: Evidence from Indonesia - Adibah, Nur; Rahmah, Maylina Syarifah; Zaenal, Muhammad Hasbi (International Journal of Zakat, 2024)
This study investigates the impact of the Human Development Index (HDI) and the Information and Communication Technology Development Index (ICT-DI) on the digital zakat in Indonesia. The HDI variable is proxied by the quality of human resources, while ICT-DI is measured by the number of internet users. This study uses a multiple linear model to analyze such an impact. Multiple regression tests are used to determine the particular effect of HDI and ICT-DI on the growth rate of digital zakat. The results show that HDI has partially a significant effect on the digital zakat growth rate. ICT-DI also has a significant and positive influence on digital zakat. At the same time, HDI and ICT-DI have a significant effect on the growth rate of digital zakat. These results have implications for increasing HDI and ICT-DI that can positively impact on the growth rate of digital zakat.